DESIGNING A 3D ROGUELIKE GAME WITH PROCEDURAL CONTENT GENERATION USING THE GRAPH GRAMMARS METHOD - Vatresia, Arie; Putra Utama, Ferzha; Yulianto, Adi (Informatika, Universitas Jenderal Soedirman, 2023)
Roguelike is a genre of role-playing video game in which the player explores dungeons through procedurally generated levels. If they lose, the player loses progress, and the character starts over again. Procedural Content Generation (PCG) is a computer program that can create game content automatically, randomly, and uniquely, either by itself or with human assistance. In this study, the 3D roguelike game was designed with players playing a character to explore dungeons. Players will enter at one point, explore the surrounding environment, defeat the enemies encountered, avoid traps, collect treasure, and finally exit at another point. Each time the player starts a new game session, the game will generate a dungeon with a mission structure that changes randomly to create a variety of gameplay. This mission generation is implemented using the Graph Grammar method. The game is built using the Unity game engine and is intended to run on Android devices. Based on the black box test results, all the game's features are running well according to their functions. The built games will be evaluated using the GUESS-18 to determine the level of player satisfaction. Based on the evaluation results, the game is included in the